Estimate of production costs and profitability of banana cultivars - Turco, Patrícia Helena Nogueira [UNESP]; Martins, Adriana Novais [UNESP]; Firetti, Ricardo [UNESP]; Pinatti, Eder; de Araújo, Humberto Sampaio [UNESP] (My University, 2022)
This work aims to compare the production cost and indicators of economic profitability of the production of the most planted and commercialized banana cultivar in the geographic microregion of Assis, São Paulo (BRS Princesa and Grande Naine). The production data and technical coefficients used in the economic simulations were obtained from the results of experimental agronomic research with the implantation of banana plantations and the execution of three production cycles in the municipality of Palmital (SP). For that, the methodology of Total Operating Cost (TOC) and the indicators of Gross Revenue, Operating Profit, Profitability Index were used; Gross Margin and Leveling Point. The results showed that the banana cultivars Grande Naine and BRS Princesa have an average Total Operating Cost (TOC) of R$21,210.78 and R$18,893.06 respectively. It was observed that the largest expenditures were with inputs. For the studied location and production system, the cultivar Grande Naine presented an average operating profit of R$ 5,049.29 higher in the three production cycles and a higher average profitability (53.36) and increasing from the first cycle onwards, unlike the observed in the other cultivar. Therefore, it is suggested that Grand Nine is more suitable for cultivation from an economic point of view when compared to BRS Princesa.
Keywords: Musa sp; Operating cost; profitability